MEDIATING ROLE OF PRODUCT INNOVATION ON MARKET AND ENTREPRENEURIAL ORIENTATION TOWARD MARKETING PERFORMANCE IN PADANG'S CULINARY SMES - Yefrina Akhyudelpa; Ratni Prima Lita; Yulia Hendri Yeni; Syafrizal Syafrizal (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study analyzes the mediating role of product innovation in the influence of market orientation and entrepreneurial orientation on the marketing performance of culinary MSMEs in the Car Free Day (CFD) area of Padang during the digital era. Using a quantitative method with purposive sampling, data were collected from 100 respondents who actively utilize digital marketing platforms and have operated for at least six months. Data analysis was performed using PLS-SEM with SmartPLS 4. The findings reveal that market orientation and entrepreneurial orientation significantly drive product innovation (β= 0.374, p < 0.05 for both), which in turn acts as a robust mediator to enhance marketing performance (β= 0.266, p < 0.05). This confirms that strategic mindsets require tangible innovative outputs, such as